ICT APPLICATION AND NATIONAL COMPETITIVENESS OF THE REPUBLIC OF SERBIA - Živković, Jelena (Economic Outlook, 2023)
Information and communication technologies (ICT) are an indispensable part of the modern economic world, and their application can improve the economic development of countries. However, ICT application requires high investment and a highly skilled workforce, which makes it difficult for developing countries to keep up with developed countries. The countries’ technological equipment is a crucial factor of national competitiveness, and within the calculation of the Global Competitiveness Index (GCI), particular emphasis is placed on the evaluation of the application of ICT. The paper deals with the Technological Readiness and the ICT аdoption analysis of Serbia from 2010 to 2019 and their individual categories. The results showed that Serbia achieved worse results over the years, and it is significantly behind the countries of the European Union in terms of the application of ICT. The worsening results in recent years show that ICT is developing much faster in the world than in Serbia.